Crystal structure of wild-type and mutant human Ap(4)A hydrolase - Ge, Honghua (Biochem Biophys Res Commun, 2013)
Ap(4)A hydrolase (asymmetrical diadenosine tetraphosphate hydrolase, EC 3.6.1.17), an enzyme involved in a number of biological processes, is characterized as cleaving the polyphosphate chain at the fourth phosphate from the bound adenosine moiety. This paper presents the crystal structure of wild-type and E58A mutant human Ap(4)A hydrolase. Similar to the canonical Nudix fold, human Ap(4)A hydrolase shows the common αβα-sandwich architecture. Interestingly, two sulfate ions and one diphosphate coordinated with some conserved residues were observed in the active cleft, which affords a better understanding of a possible mode of substrate binding.